Perbandingan Sifat Kepribadian Berdasarkan Pendekatan Ocean Antara Wirausaha Sosial Pria Dan Wanita - Anastasia Janet Saputra; Frangky Slamet (Jurnal Manajerial Dan Kewirausahaan, 2019)
The main purpose of this research is to discover the comparison of OCEAN approach’s personality traits between male and female social-entrepreneur. Selected sample in this research has been chosen by purpose sampling, which involved 60 social-entrepreneurs in Jakarta; therefore, 30 male social-entrepreneurs and 30 female social-entrepreneurs in Jakarta has been selected to be involved in this research. All data in this research are collected using quantitative research method, specifically using questionnaires. Furthermore, Likert’s scale and independent sample t-test has been used to analyze all data gathered in this research, and Statistical Package for Social Science (SPSS) version 23 program was used in the analysis process. The results of this research show that female social-entrepreneurs are tending to have the OCEAN approach’s personality traits, which consists of openness to experience, extraversion, agreeableness, neuroticism, and conscientiousness, rather than male social-entrepreneurs. Tujuan penelitian ini adalah untuk mengetahui perbandingan sifat kepribadian berdasarkan pendekatan OCEAN antara wirausaha sosial pria dan wanita. Sampel dipilih dengan menggunakan purpose sampling. Populasi penelitian ini adalah wirausaha sosial di Jakarta dengan jumlah sampel 60 wirausaha sosial di Jakarta, yang terdiri dari 30 wirausaha sosial pria dan 30 wirausaha sosial wanita. Data diukur dengan menggunakan skala Likert dan menggunakan analisis data independent sample t-test, dengan dibantu oleh program Statistical Package for Social Science (SPSS) versi 23. Hasil menunjukkan bahwa wirausaha sosial wanita lebih memiliki sifat kepribadian OCEAN (openness to experience, extraversion, agreeableness, neuroticism dan conscientiousness) daripada wirausaha sosial pria.